Enduring Emotions. Fat Time and Weight Loss in the Finnish Body Positive Podcasts Jenny and the Fat Myth Busters and The Soft - Hynnä-Granberg Kaisu (Taylor and Francis, 2022)
The article analyses two Finnish body positive podcasts, Jenny and the Fat Myth Busters and The Soft, zooming in on their way of discussing weight loss. Drawing on queer studies’ understanding of queer time, the article discusses fat time as a nonlinear temporality, which, as a product of fat-marginalizing culture, is hurtful yet characterized by a potential to resist. The article utilizes Sara Ahmed, Rebecca Coleman, and Sienne Ngai’s formulations of emotions and temporality. It utilizes the method of a situated close reading where the author’s experience with weight loss works as an important resource for analysis. The article argues that fat time is characterized by “ugly feelings that stay.” The endurance of feelings expands existing understandings of fatness by arguing that fat could be discussed as an affective presence beside it being viewed as a material reality. Even as the body changes, emotions such as anxiety and pessimism endure, making both the present and future fat.